The modern pharmacist: Is the future in the past? - Roberto Frontini (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2016)
In conclusion between a medicine with its active ingredient and the outcome of the patient there are a lot of barriers like e.g. drug formulation, patient attitude, social context, medication errors, patient's genomic, biased information. The pharmacist has to help patients in overcoming such barriers but this is only possible if he or she is part of a cure team working in collaborative way without hierarchy barriers.